The effects of gallic acid and metformin on male reproductive dysfunction in diabetic mice induced by methylglyoxal: An experimental study - Zeinab Behdarvand-Margha; Akram Ahangarpour; Mohammadreza Shahraki; Gholamreza Komeili; Layasadat Khorsandi (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Diabetes mellitus is a disease that has reached a dangerous point. Today, nearly 500 million men and women around the world live with diabetes. Gallic acid (Gal) affects diabetes. Objective: To evaluate the effects of Gal and metformin (met) on the levels of glucose, insulin, testosterone, luteinizing hormone (LH), follicle-stimulating hormone (FSH), sperm count, antioxidant status, and histological changes in the testes of diabetic mice induced by methylglyoxal (MGO). Materials and Methods: In this experimental study, 50 male adult NMRI mice, weighting 25-30 gr, aged 3-4 months were randomly divided into five equal groups (n = 10/each). (i) Control (vehicle, normal saline), (ii) MGO (600 mg/kg/d) orally for 28 days, (iii) Gal (50 mg/kg/d), (iv) MGO+Gal, and (v) MGO+met (200 mg/kg/d). Gal and met were administered orally for 21 consecutive days after the induction of diabetes. Blood samples were taken at 24 hr after the latest doses of treatment. Histological assessment of the testis was done, and the epididymis sperm count was obtained. Antioxidant indices, glucose, insulin, LH, FSH, and testosterone levels were measured. Results: In the MGO group compared to the control group, insulin, glucose (p = 0.001), LH (p = 0.04) and malondialdehyde (p = 0.001) were increased. However, the level of testosterone (p = 0.001), seminiferous tubule diameters, epithelial height, sperm count, superoxide dismutase activity (p = 0.02), and testis volume (p = 0.01) were decreased. The results indicated that Gal and met ameliorated the MGO effects. Conclusion: These findings suggested that the animals receiving MGO became diabetic. According to the results, Gal and met can effectively prevent MGO-induced diabetes. The effect of Gal was equivalent and sometimes better than metformin.